Biomechanical analysis of the penalty-corner drag-flick of elite male and female hockey players - Lopez De Subijana, C.; Juarez, D.; Mallo, J.; Navarro, E. (Sports Biomechanics, 2010)
The aim of this study was to analyse the kinematic sequencing in the penalty-corner drag-flicks of elite male and female field hockey players of international calibre. Thirteen participants (one skilled male drag-flicker and six male and six female elite players) participated in the study. An optoelectronic motion analysis system was used to capture the drag-flicks with six cameras, sampling at 250 Hz. Select ground reaction force parameters were obtained from a force platform which registered the last support of the front foot. Twenty trials were captured from each subject. Both player groups showed significantly ( p , 0.05) smaller ball velocity at release, peak angular velocity of the pelvis, and negative and positive peak angular velocities of the stick than the skilled subject. Normalised ground reaction forces of the gender groups were also smaller than that of the skilled drag-flicker. By comparing these players we established that the cues of the skill level are a wide stance, a whipping action (rapid back lift) of the stick followed by an explosive sequential movement of the pelvis, upper trunk and stick.